Relationship between Perceived Ease of Use, Perceived Usefulness and Motivation Opportunity Ability Theory in Online Gamers Know-How Exchange - Bob Foster; Fitriani Reyta; Susan Purnama (Research Collaboration Community (RCC), 2021)
Business needs to take advantage of Indonesian online gamers who are using online community to communicate and interact, when gamers share their reviews of game, for example, or when they post reviews of their purchases of virtual goods from online games. Using online community, gamers can do the trading with other members. The key is to share their experience with online games throughout the gamer’s journey.Players play an important role in the game market and have unique characteristics that respond differently to technology acceptance. In addition, a comprehensive review of the relevant literature on motivation for using Online Gamers Know-How Exchange shows that players are looking for recommendations from friends about the games they are interested in, through the social networking community and especially from their own communities.This paper analyzed the phenomenon of game-related industry involving motivation, opportunity, abilty and technology acceptance model in which organizations effectively raise the communication and know how above the gamers.Gamers from online community game taken as sample in Bandung City, West Java, Indonesia.Result shown that the two PEOU and PU were positively related to Online Gamers Know-How Exchange.